1998
DOI: 10.1021/om980048+
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Tandem [2 + 2 + 2]/[4 + 2] Cycloaddition of 1,6-Heptadiyne with Norbornene

Abstract: The ruthenium(II)-catalyzed reaction of a substituted 1,6-heptadiyne with norbornene gave a tandem [2 + 2 + 2]/[4 + 2] cycloaddition product as a single stereoisomer along with a [2 + 2 + 2] cycloadduct. CpRu(cod)Cl catalyzes both [2 + 2 + 2] cycloaddition of the heptadiyne and norbornene and subsequent [4 + 2] cycloaddition of the resultant cyclohexadiene and norbornene. The second [4 + 2] cycloaddition step was effectively improved by use of an indenyl complex, (η5-C9H7)Ru(PPh3)2Cl, to afford the tandem addu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…For example, [(g 5 -C 9 H 7 )RuCl-(PPh 3 ) 2 ] showed efficient catalytic activity and selectivity for the redox isomerisation of allyl and propargyl alcohols [2], dynamic kinetic resolution of racemic alcohols [3], and the cycloaddition of 1,6-heptadiyne with bicycloalkenes [4], when compared to its cyclopentadienyl analogue, [CpRuCl(PPh 3 ) 2 ]. Cyclopentadienyl complexes of ruthenium have been reported as an excellent catalyst for many organic reactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, [(g 5 -C 9 H 7 )RuCl-(PPh 3 ) 2 ] showed efficient catalytic activity and selectivity for the redox isomerisation of allyl and propargyl alcohols [2], dynamic kinetic resolution of racemic alcohols [3], and the cycloaddition of 1,6-heptadiyne with bicycloalkenes [4], when compared to its cyclopentadienyl analogue, [CpRuCl(PPh 3 ) 2 ]. Cyclopentadienyl complexes of ruthenium have been reported as an excellent catalyst for many organic reactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…Substantial amounts of a different kind of tandem 1:2 adducts (6) were isolated (ref. 5). The yields of 6 significantly increased when Ru(Indenyl)Cl(PPh3)2 was employed as the catalyst (Table 1).…”
Section: Introductionmentioning
confidence: 97%
“…It has been reported that cyclotrimerization of alkynes, co-cyclotrimerization of two alkynes with unsaturated organic compounds containing the C=X bond (X = C, O, S, N, etc.) [8][9][10][11][12][13][14][15][16][17][18][19], and oxidative couplings of alkynes [20][21][22][23][24] could be mediated by organoruthenium complexes. The commonly used Ru complexes are pseudo 14-electron species Cp′Ru(COD)L (Cp′ = C 5 H 5 , C 5 Me 5 ; COD = 1,5-cyclooctadiene; L = Cl, Br) and the cationic complexes [Cp′RuL-(NCCH 3 ) 2 ] + (L = CH 3 CN, PR 3 , AsR 3 , SbR 3 , CO) and [Ru( 5 -C 5 H 4 CH 2 CH 2 - 1 P-PPh 2 )(CH 3 CN) 2 ] + .…”
Section: Introductionmentioning
confidence: 99%
“…The resultant Ru complex [ 5 :-Me 2 C(C 5 H 4 )-(C 2 B 10 H 10 )]Ru(NCCH 3 ) 2 (1) shows a diverse reactivity pattern toward alkynes. It reacts with silylalkynes Me 3 SiCCH or Me 3 SiCCSiMe 3 to yield a bis(vinylidene)ruthenium complex [ 5 :-Me 2 C(C 5 H 4 )(C 2 B 10 H 10 [34]. Treatment of 1 with 3 equiv of ArCCH yielded unexpected ruthenium complexes bearing a tricyclic moiety [ 4 :-Me 2 C(C 11 H 7 Ar 3 ) (C 2 B 10 H 10 )]Ru(NCCH 3 ) (Scheme 1) [35].…”
Section: Introductionmentioning
confidence: 99%